Evaluasi Perbandingan Scoring Proposed Value dan Perceived Value Berdasarkan Model UX Honeycomb (Studi Kasus: Traveloka, Tiket.com, Dan Pegi-Pegi) - Dina Ayu Musfikasari; Hanifah Muslimah Az-Zahra; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In the product which are offered usually have value to proposition that users feel while access or use it. Value proposition design is aimed to fill demand, experience, and desire of user in using it. In that condition, it can be used in development of online application based on Android platform and web-based to order ticket. Some of them for example Traveloka, Tiket.com, and Pegi-pegi. In this research, the writer use UX Honeycomb method to compare the value that system gives with user feel based on UX Honeycomb aspect. The goals of this research are to know result of proposed value analyze and perceived value analyze, and to know the comparison of proposed value and perceived value in Traveloka, Tiket.com, and Pegi-pegi. The methodology of this research is started from reference's study, value analyst, value scoring, taking and processing data to gain perceived value score, comparison of proposed value and perceived value, and making conclusion. Based on the result of analysis and discussion of each application that has done include all of UX Honeycomb aspect, in Traveloka application, the aspect which need to be improved is useful, in Tiket.com, aspect which need to be improved are usable and credible. Whereas in Pegi-pegi application, aspect which need to be improved are usable and desirable.